The Impact of Sexually Transmitted Infections on Male and Female Infertility: Literature Review - Yunita Amraeni; Hasda; Abdul Kadir Bahar; Wa Ode Israyani (Universitas Mandala Waluya, 2023)
Sexually Transmitted Infections (STI) are a global issue with 374 million new infections globally and a prevalence of 6% in 2022 in Indonesia. Sexually transmitted infections have potential causes of infertility. The purpose of this study is to describe the impact of STIs on infertility for both men and women. The research design is a literature review by looking systematically at journals and articles on Google Scholar, Garuda Portal, and Science Direct. The inclusion criteria in this study were journal publications spanning 2018-2022, the outcome studied was to find out that sexually transmitted infections have an impact on the incidence of infertility in men and women. Reviews of 5 selected articles describing the correlation between sexually transmitted infections and infertility, including reviews of men with Chlamydia trachomatis or men and women positive for Human papillomavirus or women with vaginal lactobacilli have the potential for infertility. Microbiological association with experiments using IVF (In Vitro Fertilisation) or pregnancy attempts using IVF shows that 85.7% of microbiologically positive couples have a success rate of 7.5%. Therefore, it can be concluded that sexually transmitted infections have an impact on the incidence of infertility, especially in men compared to women, which are mostly caused by bacteria and viruses that cause sexually transmitted infections. In addition to sexually transmitted infections, it is also caused by poor lifestyle factors such as using drugs, alcoholic beverages and smoking. Efforts are needed to detect symptoms of infertility early, especially in STI sufferers with HIV and AIDS cases.